Comparison of Efficacy of Tofacitinib versus Betamethasone Pulse Therapy in the Treatment of Vitiligo: Tofacitinib Versus Betamethasone Pulse Therapy in the Treatment of Vitiligo - Shafquat, Hira; Ahmed, Hafiz Bashir; Memon, Abeer; Shah, Madiha; Memon, Nazish; Khan, Bedar Bakhat (Pakistan Journal of Health Sciences, 2024)
Vitiligo is a chronic autoimmune skin disorder characterized by depigmentation due to melanocyte destruction, significantly impacting patients’ quality of life. Emerging treatments, including Janus kinase inhibitors like tofacitinib, offer promising alternatives to conventional therapies such as corticosteroids. Objective: To compare the efficacy of tofacitinib with betamethasone pulse therapy in achieving re-pigmentation in vitiligo patients. Methods: This quasi experimental study was conducted on 42 patients of vitiligo of either gender with ages between 12 and 65 years and had a history of vitiligo for over one year with a body surface area affected by vitiligo exceeding 5%, and a vitiligo area scoring index score of more than 10 were included in the study. Patients were divided into 2 equal groups using alternate assignments. Group A were treated with betamethasone pulseerapy of 4mg twice a week. Group B were treated with tofacitinib at a dose of 5 mg twice a day. Results: Optimal recovery (vitiligo area scoring index decrease ≥20% from baseline) was observed in 14 (66.7%) of the tofacitinib group compared to 6 (28.6%) in the betamethasone group, highlighting tofacitinib’s superior efficacy in achieving significant vitiligo area scoring index reduction. Over three months, the BSA affected by vitiligo decreased in both groups, with a significantly greater reduction in Group B (tofacitinib) compared to Group A (betamethasone). Conclusions: It was concluded that tofacitinib may be more effective than betamethasone pulse therapy in reducing both the extent and severity of vitiligo.